The growth drivers : the definitive guide to building marketing capabilities - Bird, Andy.; McEwan, Mhairi (Hoboken, N.J. : Wiley, 2012)
"The Growth Drivers is not only a practical guide to building marketing capabilities it explains why it is critical that organisations invest in the capabilities needed to excel at customer-centric marketing to drive growth"--
pt. 1. Understanding the growth drivers -- pt. 2. How to transform marketing capabilities to drive growth -- pt. 3. Sustaining growth in practice.
Includes bibliographical references and index.
Keywords: Market segmentation; Economic development; Investments; BUSINESS & ECONOMICS -- Green Business; Economic development; Investments; Market segmentation; Electronic books